The Role of Evidence in Politics: Motivated Reasoning and Persuasion among Politicians. Issue 3 (18th August 2017) - Baekgaard, Martin; Christensen, Julian; Dahlmann, Casper Mondrup; Mathiasen, Asbjørn; Petersen, Niels Bjørn Grund
Abstract : Does evidence help politicians make informed decisions even if it is at odds with their prior beliefs? And does providing more evidence increase the likelihood that politicians will be enlightened by the information? Based on the literature on motivated political reasoning and the theory about affective tipping points, this article hypothesizes that politicians tend to reject evidence that contradicts their prior attitudes, but that increasing the amount of evidence will reduce the impact of prior attitudes and strengthen their ability to interpret the information correctly. These hypotheses are examined using randomized survey experiments with responses from 954 Danish politicians, and results from this sample are compared to responses from similar survey experiments with Danish citizens. The experimental findings strongly support the hypothesis that politicians are biased by prior attitudes when interpreting information. However, in contrast to expectations, the findings show that the impact of prior attitudes increases when more evidence is provided.